Chirped SAW devices for wireless passive sensors - Reindl, Leonhard; Rösler, Ulrike; Ruppel, Clemens; Obertreis, Robert; Weigel, Robert (Ultrasonics Symposium, 1997)
Chirped structures as sensing elements in a delay line allow for the variation of the sensitivity over a wide range. A sensor system operating at a center frequency of 434 MHz and a system bandwidth of 1.7 MHz will be shown. We designed dispersive inline SAW structures with two chirped and apodized IDTs. Two expanders, one with an up- and the other with a down-chirp, have been built on quartz 37.5° cut. The corresponding compressors (down- and up-chirp) are the sensor elements and have a wider bandwidth to compensate for the frequency shift due to the sensor effect. The compressors have been built on quartz for mechanical sensing and on LiNbO3, YZ-cut for temperature sensing. To avoid bulk wave conversion we used a modulated IDT with 8 electrodes per electrical period. On quartz we operated these IDTs on the 3rd and on LiNbO3 on the 5th harmonic which is lower than the onset frequency for bulk wave conversion and gives a suitable impedance level as well. We present theoretical and experimental results for the devices and show results of the corresponding sensor systems for temperature.
elib2cris::1512001600,reindl1997a
Keywords: Bandwidth; Chirp; Compressors; Delay lines; Frequency; Mechanical sensors; Sensor systems; Surface acoustic wave devices; Temperature sensors; Wireless sensor networks